Teaching Strategies For Speaking Skills: Teachers’ Implementation and Students Opinion - Titan Meuthia Annisa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The major objective of this study is to examine teachers' strategies in teaching speaking and students' opinions of the teachers' strategies in an online class. The study enrolled two English teachers and two students from each teacher. The descriptive qualitative technique was employed in this study, with an emphasis on the teachers' strategies, and interviews as data collection. The results of this study indicated that teachers employed several strategies while teaching speaking during an online class, including establishing a clear objective, showing and explaining the lesson, integrating prior knowledge through question and answer activities, providing more practice, providing students with feedback, and remaining flexible to allow students time to learn. The students' responses to the teacher's techniques were incredibly positive. Students feel encouraged and truly appreciate the teaching and learning process, despite possible obstacles. As a result, teachers' strategies for teaching speaking are important during an online class.